ANALISIS POLA KONVERSI LAHAN SAWAH DAN STRUKTUR HUBUNGAN PENYEBAB DAN PENCEGAHANNYA (STUDI KASUS KABUPATEN SUBANG, PROVINSI JAWA BARAT) - Paulus Basuki Kuwat Santoso; Widiatmaka Widiatmaka; Supiandi Supiham; Machfud Machfud; I Wayan Rusastra (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2017)
The extent of land use and land cover (LULC) of paddy field in Subang Regency has decreased because of the conversion into non-paddy field. The objectives of this research were to review the spatial pattern of LULC change, to analyze the cause and to identify the anticipation strategy of paddy field conversion. The analysis used the Landsat data of 1999, 2004, 2009, and 2014 which were interpreted by supervise technique. The interpretation result was compared with the existing LULC and was examined by Kappa methode. This research focuses on the spatial pattern of LULC change, integrated with the Interpretative Structural Modeling (ISM) to review the cause and the anticipation strategy of the conversion. The results revealed that the paddy field was converted into plantation, built-up area, and dryland agriculture. The ISM result revealed that the conversion causes were: (1) increasing the farmer economic needs, (2) increasing the built-up area, (3) increasing the selling price of land and (4) decreasing the farming motivation. To anticipate the conversion, several priorities are needed, namely (1) rehabilitation of the irrigation infrastructures and regulation of the spatial planning, (2) tighten the conversion permit and maximization of the abandoned land, and (3) giving the incentive and disincentive for the farmers, land consolidation, and establishment of corporate farming.